(3GdehWCs - (3eGdc Hf CfS Hf eGdc GdCUHMj GdMejQj, CHh YHO Gddg, J (B179 (3g` s ((3GdLGeY GdCRgQ s)
(3ChdgG (B:s
(3CHhGH GdUdGI (B: (3HGH ehGbjJ GdUdGI GNHQfG GdTjN GdLdjd GdSjO CHh GdMSf Ydi Hf GdMSjf Hf Ydi GHf CjhH GdHRGR s
(3BNQgG (B:s
(3HGH GdJaSjQ hBNQ eG ajg (B: (3gPG BNQ GLRGA cJGH GdGNJdGa Hjf eGdc Hf CfS heMeO Hf GdMSjf QVi Gddg YfgeG hdG Mhd hdG bhI EdG HGddg GdYdi GdYXje s
(3QhGjI eMeO Hf GdMSfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B257 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B168s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1907s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda SfI (B719s
Keywords: (3GdMOjK h GdeUWdMs